Benchmarking with a Language Model Initial Selection for Text Classification Tasks - Agus Riyadi; Mate Kovacs; Uwe Serdült; Victor Kryssanov (Machine Learning and Knowledge Extraction)
The now-globally recognized concerns of AI’s environmental implications resulted in a growing awareness of the need to reduce AI carbon footprints, as well as to carry out AI processes responsibly and in an environmentally friendly manner. Benchmarking, a critical step when evaluating AI solutions with machine learning models, particularly with language models, has recently become a focal point of research aimed at reducing AI carbon emissions. Contemporary approaches to AI model benchmarking, however, do not enforce (nor do they assume) a model initial selection process. Consequently, modern model benchmarking is no different from a “brute force” testing of all candidate models before the best-performing one could be deployed. Obviously, the latter approach is inefficient and environmentally harmful. To address the carbon footprint challenges associated with language model selection, this study presents an original benchmarking approach with a model initial selection on a proxy evaluative task. The proposed approach, referred to as Language Model-Dataset Fit (LMDFit) benchmarking, is devised to complement the standard model benchmarking process with a procedure that would eliminate underperforming models from computationally extensive and, therefore, environmentally unfriendly tests. The LMDFit approach draws parallels from the organizational personnel selection process, where job candidates are first evaluated by conducting a number of basic skill assessments before they would be hired, thus mitigating the consequences of hiring unfit candidates for the organization. LMDFit benchmarking compares candidate model performances on a target-task small dataset to disqualify less-relevant models from further testing. A semantic similarity assessment of random texts is used as the proxy task for the initial selection, and the approach is explicated in the context of various text classification assignments. Extensive experiments across eight text classification tasks (both single- and multi-class) from diverse domains are conducted with seven popular pre-trained language models (both general-purpose and domain-specific). The results obtained demonstrate the efficiency of the proposed LMDFit approach in terms of the overall benchmarking time as well as estimated emissions (a 37% reduction, on average) in comparison to the conventional benchmarking process.